Definición de un ciclo de conducción representativo para taxis eléctricos en la ciudad de Loja - Jaramillo Merino, Pablo Rafael (2022)
This study aims to create the Typical Driving Cycle (TDC) of an electric cab while circulating with passengers in Loja, Ecuador. To accomplish this purpose, real-time data was recorded over a 24-day period to the vehicle in free travel. Among the parameters recorded were linear speed, altitude, vehicle position, current and battery voltage. As part of the methodology, EU Regulation 646 was used to perform the smoothing of the slope profile.To determine the wheel force needed to move the unit, additional environmental data and variables provided by the vehicle manufacturer were required, as well as parameters obtained through calculation. Consequently, by programming in Matlab Simulink, the energy consumption per force was obtained, in order to use the methodology of Minimum Weighted Differences of Characteristic Parameters (MWD-CP) to obtain the TDC. The cab performed 660 rides in total and the results indicate that the fifth ride performed on day eleventh, represents the TDC, which has a duration of 9 minutes and 8 seconds, a maximum speed of 45 km/h, an average speed of 22.32 km/h, a distance traveled of 3.4 km and wheel energy consumption of 0.58 kWh. Furthermore, the average battery energy efficiency was 8.44 km/kWh. For all local citizens, this driving cycle is of paramount importance, since it will serve as the basis for future research, evaluation of the impact on traffic, autonomy, and state of charge, among other factors. Keywords: Electric taxis, Typical Driving Cycle, Minimum Weighted Differences, energy efficiency.